2013
DOI: 10.1016/j.ophtha.2013.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Hysteresis as a Risk Factor for Glaucoma Progression: A Prospective Longitudinal Study

Abstract: Purpose To evaluate the role of corneal hysteresis (CH) as a risk factor for the rate of visual field progression in a cohort of glaucoma patients followed prospectively over time. Design Prospective observational cohort study. Participants The study group included 114 eyes of 68 glaucoma patients followed for an average of 4.0 ± 1.1 years. Visual fields were obtained with standard automated perimetry. Included eyes had a median number of 7 (range: 5 to 12) tests during follow-up. Methods CH measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
228
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(247 citation statements)
references
References 41 publications
12
228
3
4
Order By: Relevance
“…[15][16][17] We noted only modest Pearson correlations (À0.15 to À0.20) between CRF and VCDR (clinical and HRT) in our subjects. Although Vu et al 18 showed similar weak associations (r ¼ À0.11 to À0.15) of VCDR with CH, they did not report on the association with CRF.…”
Section: Discussioncontrasting
confidence: 60%
“…[15][16][17] We noted only modest Pearson correlations (À0.15 to À0.20) between CRF and VCDR (clinical and HRT) in our subjects. Although Vu et al 18 showed similar weak associations (r ¼ À0.11 to À0.15) of VCDR with CH, they did not report on the association with CRF.…”
Section: Discussioncontrasting
confidence: 60%
“…Lower CH has been reported to be associated with glaucomatous visual field progression in retrospective studies [11,13,28] and in one prospective study [12]. Anand et al found that lower CH was associated with worse eyes in asymmetric POAG [29].…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the impact of these parameters on the accuracy of Goldmann applanation tonometry (GAT) [5][6][7][8][9][10], it has been shown that these parameters are significantly reduced in glaucoma patients and appear to be a risk factor for glaucoma progression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, people with axial myopia are more susceptible to OAG (Boland and Quigley, 2007) and their eyes have mechanical disadvantages in responding to the stress of IOP because of their larger globe diameter and thinner sclera. Third, hysteresis measured by an ocular response analyzer is a risk factor for OAG progression (Congdon et al, 2006;Medeiros et al, 2013). Fourth, in human glaucoma eyes, scleral rigidity is estimated to be increased by indirect measurements in vivo (Ebneter et al, 2009;Hommer et al, 2008) and by in vitro inflation studies .…”
Section: Pathological Changes In the Sclera And Onh In Glaucomamentioning
confidence: 99%